“Innovaciones tecnológicas preventivas de la degradación ambiental por residuos peligrosos en los cultivos de maíz (zea mays) de la zona norte de la provincia de Los Ríos” - Ferrin Contreras, Genesis Jael (2020)
The province of Los Ríos is one of the most important in the Republic of Ecuador for having the richest hydrographic distribution in the country and for its activities such as trade, industry, livestock and agriculture. Farmers are unaware of the problem of chemical pollution from their activities; this has contributed to environmental deterioration, because there is a need to adopt substantial changes in agricultural practices. It follows that the generation of ideas and inventions is of great use to farmers, and therefore research strategies of technological innovations to prevent environmental degradation by hazardous waste in maize crops. 260 farmers were surveyed in five cantons in the northern region of Los Rios province, using a questionnaire that considered aspects such as the quality and prices of agricultural inputs, investigating the adoption status of farmers and also considering the perception of farmers about the effects of biofertilizers on their environment and lives. Additionally, in greater detail it was determined that the cantons Mocache, Ventanas, Puebloviejo and Quinsaloma present a great similarity to being adoptive and having a negative perception toward the warehouses of the country that commercialize the agricultural inputs, however, Quevedo has significant differences as one of the least adoptive cantons and a somewhat positive perception of the price and quality of the products, on the other hand, it was determined that only 36,15% of the respondents used biofertilizers, and the status of farmers' perception of the effect of biofertilizers was determined, which gave a positive result on the part of the farmers toward the three categories. In the design of the strategies, they were provided with information according to their basic needs to determine the strategy of their preference. The comparison of the adoptive ranges was made by means of the PERMANOVA non parametric multivariate test, with significant differences (F:22.82; p:0.0001) and it was observed that there is similarity between the cantons Mocache, Puebloviejo, Ventanas and Quinsaloma